Quantification of sex pheromone from Anocentor nitens by gas chromatography-mass spectrometry-selected ion monitoring - Rodrigues, Clenilson M. [UNESP]; Borges, Lígia M.F.; Ferri, Pedro H.; Faria, Lourival C. (Elsevier, 2004)
Two highly sensitive and selective methods based on gas chromatography coupled to mass spectrometry (GC-MS) in the selected ion monitoring (SIM) mode have been developed for the quantification of 2,6-dichlorophenol (2,6-DCP), a sex pheromone of the tick females of Anocentor nitens. Standard addition method and calibration curve techniques using 5-bromine-4-hydroxy-3- methoxybenzaldehyde (5-BrV) as internal standard (IS) afforded detection limit of 0.1ngml-1. The calibration curve was linear over the concentration range from 0.5 to 500ngml-1 for 2,6-DCP. Results show that the concentration range of sex pheromone in the extracts samples was 1.08-10.35ngml-1. The methods developed provided reliable procedures to determine amounts of 2,6-DCP present in ticks. © 2003 Elsevier B.V. All rights reserved.
Keywords: 2,6-Dichlorophenol; Anocentor nitens; GC-MS-SIM; Calibration; Gas chromatography; Mass spectrometry; Detection limits; Phenols; 2,6 dichlorophenol; 5 bromine 4 hydroxy 3 methoxybenzaldehyde; benzaldehyde derivative; sex pheromone; unclassified drug; calibration; controlled study; extraction; female; gas chromatography; hormone determination; ion monitoring; mass spectrometry; nonhuman; quantitative analysis; sex difference; standard; technique; tick